The promising form of supporting the treatment of depression - Izabela Halczuk; Bartłomiej Stachura; Justyna Górska; Samanta Gawryszczak; Anna Gliwa; Katarzyna Nowak (Kazimierz Wielki University, 2024)
Introduction and purpose Recently, there has been a significant increase in interest in the dynamically developing field of science, nutripsychiatry, which has contributed to an increase in the number of studies conducted assessing the relationship between the use of a vegetarian nutritional model and its potential therapeutic impact on holistically understood mental health. Material and methods For the purposes of this work, a review of the literature available in the PubMed and Google Scholar search engines, was performed using the following keywords: vegetarian diet; depression; psychiatry. Works published before 2015 were excluded from the analysis. During the review of the literature of available scientific texts, attempts were made to comprehensively present the state of current knowledge. State of knowledge Numerous clinical studies support the beneficial effect of a vegetarian diet on mood by improving well-being and lower levels of anxiety and depression. However, there are also studies that did not show a relationship between the diet and the mood of the subjects, as well as studies indicating possible dangers associated with the use of this nutritional model. Conclusions The use of a vegetarian dietary pattern as a potential intervention is a promising method of non-pharmacological support. The amount of available scientific data confirming the beneficial effect of a vegetarian diet on mental health is insufficient to recommend it as a standard form of supporting the treatment of depression. Before implementing a vegetarian nutritional model, it is necessary to assess its safety in the patient and individualize dietary recommendations.